A Critical Analysis of South African Anti-Money Laundering Legislation with regard to Cryptocurrency - Erasmus, Deon; Bowden, Susan (Obiter, 2020)
Cryptocurrencies are decentralised virtual currencies, using blockchain technology to process peer-to-peer electronic payments. In 2009, the first successful cryptocurrency, Bitcoin, was established. This article discusses concepts of cryptocurrency, its relevance in the financial sector, its associated risks and establishes whether regulatory interference is necessary in order to combat money laundering using cryptocurrency. Currently, cryptocurrencies remain unregulated in South Africa. The article concludes that regulatory intervention is necessary and that cryptocurrencies should be integrated into relevant existing legislation.